(untitled) - Marx, Karl (London, 1964)
The whole provides new materials of the greatest importance for all who are interested in the development of Marxist thought and the general problems of the historical succession of economic formations.
Keywords: Capitalist,Economics,Chủ nghĩa tư bản,Kinh tế học